Drying kinetics and colour analysis of Moringa oleifera leaves - Ali, Muhammad Azhar; Yusof, Yus Aniza; Chin, Nyuk Ling; Ibrahim, Mohd Nordin; Basra, Shahzad Maqsood Ahmad (Elsevier, 2014)
The drying kinetics of (Moringa Oleifera) leaves was investigated at different oven drying temperatures (40, 50 and 60°C) using an established drying mathematical model. The experimental drying data of moringa leaves on the basis of reduced chi-square (χ2) and coefficient of determination (R2), the mathematical model exposed the best fit to the drying curves. The values of coefficient of determination (R2) and reduced chi-square (χ2) at 50°C temperature was (0.998 to 0.999) and (0.009 to 0.0002) respectively. Oven dry at 40°C reveled optimum colour values.